Implementation of Project-Based Science Learning to Improve Literacy of School Managers About New Renewable Energy in West Halmahera - Swandi, Ahmad; Viridi, Sparisoma; Rahmadhanningsih, Sri; Sutjahja, Inge Magdalena; Sari, Juwita (Kasuari: Physics Education Journal (KPEJ), 2024)
Renewable energy is a very important solution in overcoming the limitations of electrical energy in schools. The number of schools that have not received electricity in West Halmahera is still quite large, this hampers various daily activities in the school environment. Therefore, it is very important to provide understanding and skills about the application of new and renewable energy, especially for school managers. This study aims to improve the scientific literacy of school managers in West Halmahera about New and Renewable Energy. The type of research used is a pre-experimental research design with One-Group Pretest-Postets Design. The research sample was taken from the population of school administrators in West Halmahera with 20 school administrators. The analysis of the research results was carried out in a quantitative descriptive manner. Based on the results of the initial and final tests, an N-Gain value of 0.41 was obtained which indicates that there is an increase in literacy about renewable energy in the medium category. In addition, the results of observations show that the activity of school managers in participating in activities is quite good, which is indicated by the percentage above 70%.